Fatigue performance of joints executed in pure titanium structures with several diameters - Costa Nunez-Pantoja, Juliana Maria; Vaz, Luis Geraldo [UNESP]; de Arruda Nobilo, Mauro Antonio; Mesquita, Marcelo Ferraz (Japanese Soc Dental Materials Devices, 2011)
This study evaluated fatigue strength of CP-Ti laser-welded joints. Sixty (20/diameter) CP-Ti casted dumbbell rods with diameters of 1.5, 2.0, and 3.5 mm were sectioned and welded using two joint openings (0.0 (00) and 0.6 mm (06)). Six groups were formed, amounting to a total of 9 (n=10) with inclusion of intact groups. Welding was executed using 360 V/8 ms (1.5 and 2.0 mm) and 380 V/9 ins (3.5 mm). Joints were finished, polished, and submitted to radiographic examination to visually analyze presence of porosity (PP). Specimens were submitted to cyclic tests, and the number of cycles until failure (NC) was recorded. Fractured surfaces were examined by SEM. Kruskal-Wallis and Dunn (alpha=0.05) tests demonstrated that NC was lower for all diameters with 06, and for 3.5 mm/00. NC and PP were found to have a negative correlation (Spearman Coefficient). For CP-Ti frameworks with thin diameters, laser welding is better when structures are juxtaposed.
Keywords: Titanium; Laser welding; Fatigue; Material resistance; Mechanical cycling